Essay competition (2023) on Erich Kästner’s quote “All the mischief that happens is not only the fault of those who do it, but also of those who do not prevent it” and its meaning for me, us and our society today - Dyballa, Jacqueline; Schagan, Yuliana; Hristova, Mihaela; Stankova, Gabriela; Ivanov, Kaloyan; Peytchev, Nicolette; Antov, Yavor (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
Essays awarded in the essay competition (2023) on Erich Kästner’s quote “All the mischief that happens is not only the fault of those who do it, but also of those who do not prevent it”